Scars that won't go way - Abd Razak, Dzulkifli (2007)
The exhibits are an effective way of reminding us how fortunate we are, and how not to take for granted the prevailing peace and harmony among Malaysians. "BARBARIC" is perhaps a rather polite choice of word to describe what I saw at the weeklong exhibition on the fourth floor of PWTC which ended on Feb 11. Although it was make belief, it was certainly real enough for just about anyone who has not been in an actual war zone before. The organisers of the international conference and exhibition on "Expose War Crimes: Criminalise War" showed how barbaric war can be. On exhibit were images from Hiroshima and Nagasaki towards the end of World War II to My Lai during the Vietnam War, and in the Middle East, from Palestine to Qana and Iraq.